Engineering an integrated electroactive dressing to accelerate wound healing and monitor noninvasively progress of healing. (August 2022) - Nguyen, Nhien; Lin, Zong-Hong; Barman, Snigdha Roy; Korupalli, Chiranjeevi; Cheng, Ji-Yen; Song, Ni-Xuan; Chang, Yen; Mi, Fwu-Long; Song, Hsiang-Lin; Sung, Hsing-Wen; Lin, Yu-Jung
Abstract: Traditional wound dressings neither promote the cellular activities that heal wounds nor support the monitoring of the progress of that healing. This work develops an engineered electroactive dressing that comprises a layer of polydopamine-crosslinked carboxymethyl chitosan conductive hydrogel and an interdigitated array (IDA) electrode. The dressing is evaluated in a mouse model with a full-thickness skin defect. The conductive hydrogel provides a channel that transmits endogenous bioelectrical signals to the wound; these stimulate electrical stimuli-responsive cells, and thereby accelerate the restoration of the wounded tissue. The IDA electrode detects the electrical resistance or output current across the wounded tissue for the noninvasive real-time monitoring of the overall healing process. This wound monitoring system is integrated with a WIFI-based system for wireless data collection and transmission using a personal smartphone. Such a real-time wound monitoring system can be worn by patients, to whom it issues early warnings of potential infections and it wirelessly sends data on the progression of healing to remote medical staff for dynamic intervention as required. Graphical Abstract: ga1 Highlights: The as-designed electroactive dressing promotes wound healing and monitors its progress. The incorporated conductive hydrogel accelerates the restoration of wounded tissues. The monitoring system is integrated with a self-powered triboelectric nanogenerator. The monitoring system detects the electrical resistance or current across wound tissue noninvasively.